If graffiti changed anything, it would be illegal. The influence of political graffiti on the perception of neighborhoods and intergroup attitudes - Pollmanns, Claas; Asbrock, Frank (Frontiers in Psychology, 2023)
In a series of three studies (total N = 956), we examined how political graffiti, which serves as a representation of prevailing social norms, influences the evaluation of social cohesion and neighborhood inhabitants depending on the individuals political orientation. In line with our hypothesis, results of Study 1 (N = 199) indicated that individuals tended to express more positive evaluations of the social cohesion within a neighborhood when the political graffiti aligns with their own political orientation. Conversely, when confronted with counter-attitudinal political graffiti, participants reported lower evaluations of social cohesion. In Study 2, a sensitive scale to assess social cohesion was developed. Study 3 (N = 550) investigated the dose–response relationship of right-wing political graffiti and replicated the results from Study 1. Consistent with our hypotheses, even a minimal presence of right-wing graffiti exerted a significant impact on participants’ evaluations of the neighborhood and interacted with the participants political orientation. Taken together, our studies shed light on the crucial role of the individuals’ own political orientation for the evaluation of neighborhoods and their inhabitants. Furthermore, we offer insights into how these perceptions may influence intergroup attitudes toward foreigners living in Germany. The implications of our findings are highly relevant to ongoing discussions surrounding social norms within neighborhoods. By highlighting the significance of political graffiti as a representation of social norms, our research contributes to a deeper understanding of the dynamics at play in evaluating neighborhoods and their social fabric.